Exercise prevents β-aminopropionitrile-induced morphological changes to type I collagen in murine bone - Hammond, Max A (Bonekey Rep, 2015)
This study evaluated the effects of reduced enzymatic crosslinking, exercise and the ability of exercise to prevent the deleterious impact of reduced crosslinking on collagen D-spacing. Eight-week-old female mice were divided into four weight-matched groups receiving daily injections of either phosphate-buffered saline (PBS) or 300 mg kg(−1) β-aminopropionitrile (BAPN) while undergoing normal cage activity (Sed) or 30 min per day of treadmill exercise (Ex) for 21 consecutive days. BAPN caused a downward shift in the D-spacing distribution in Sed BAPN compared with Sed PBS (P<0.001) but not in Ex BAPN (P=0.429), indicating that exercise can prevent changes in collagen morphology caused by BAPN. Exercise had no effect on D-spacing in PBS control mice (P=0.726), which suggests that exercise-induced increases in lysyl oxidase may be a possible mechanism for preventing BAPN-induced changes in D-spacing. The D-spacing changes were accompanied by an increase in mineral crystallinity/maturity due to the main effect of BAPN (P=0.016). However, no changes in nanoindentation, reference point indentation or other Raman spectroscopy parameters were observed. The ability of exercise to rescue BAPN-driven changes in collagen morphology necessitates further research into the use of mechanical stimulation as a preventative therapy for collagen-based diseases.